Emerging Fungal Infections: New Patients, New Patterns, and New Pathogens - Daniel Z.P. Friedman (Journal of Fungi, 2019)
The landscape of clinical mycology is constantly changing. New therapies for malignant and autoimmune diseases have led to new risk factors for unusual mycoses. Invasive candidiasis is increasingly caused by non-albicans Candida spp., including C. auris, a multidrug-resistant yeast with the potential for nosocomial transmission that has rapidly spread globally. The use of mould-active antifungal prophylaxis in patients with cancer or transplantation has decreased the incidence of invasive fungal disease, but shifted the balance of mould disease in these patients to those from non-fumigatus Aspergillus species, Mucorales, and Scedosporium/Lomentospora spp. The agricultural application of triazole pesticides has driven an emergence of azole-resistant A. fumigatus in environmental and clinical isolates. The widespread use of topical antifungals with corticosteroids in India has resulted in Trichophyton mentagrophytes causing recalcitrant dermatophytosis. New dimorphic fungal pathogens have emerged, including Emergomyces, which cause disseminated mycoses globally, primarily in HIV infected patients, and Blastomyces helicus and B. percursus, causes of atypical blastomycosis in western parts of North America and in Africa, respectively. In North America, regions of geographic risk for coccidioidomycosis, histoplasmosis, and blastomycosis have expanded, possibly related to climate change. In Brazil, zoonotic sporotrichosis caused by Sporothrix brasiliensis has emerged as an important disease of felines and people.